Experimental Study of the Effect of Fuel Type on the Emitted Emissions from SIE at Idle Period - Chaichan, Miqdam T.; Abaas, Khalil I; Mohammed, Bashar A (Al-Khwarizmi Engineering Journal, 2018)
The present study investigated the impact of fuel kind on the emitted emissions at the idling period. Three types of available fuels in Iraq were tested. The tests conducted on ordinary gasoline with an octane number of 82, premium gasoline with an octane number of 92, and M20 (consist of 20% methanol and 80% regular gasoline). The 2 liters Mercedes-Benz engine was used in the experiments.The results showed that engine operation at idle speed emits high levels of CO, CO2, HC, NOx and noise. The produced emission levels depend highly on fuel type. The premium gasoline (ON=92) represents the lower emissions level except for noise at all idling speed. Adding methanol to ordinary gasoline (ON=82) showed high levels of emitted CO, CO2, HC compared with premium gasoline. Emitted NOx emissions were near zero levels for most of the idle speeds for the tested fuels.